Functional interactions between the fossa ischioanalis, levator ani and gluteus maximus muscles of the female pelvic floor: a prospective study in nulliparous women - Soljanik, Irina (Archives of gynecology and obstetrics, 2012)
Purpose: We evaluated the role of the fossa ischioanalis (FI) in functional relations between the levator ani (LA) and gluteus maximus muscles (GM) in healthy female volunteers.MethodsTwenty-three nulliparae were examined. Electromyogramms of LA and GM were simultaneously recorded during voluntary contraction of the pelvic floor muscles (PFM) and at rest in six body positions. The surface areas of LA (LAA), FI (FIA) and GM (GMA) were evaluated using MRI. Results: Simultaneous LA and GM contractions were electromyographically observed irrespectively of body position in 97.2 %. MRI revealed synchronous movement of all structures: while LAA (−7.4 %) reduced, GMA increased (+6.8 %), FIA changed significantly (+3.4 %). Conclusions: The LA, FI and GM are morphologically and functionally connected. We recommend considering these structures as the ‘LFG-Complex’, emphasising the importance of this unit for functional integration of the pelvic floor. The findings of this study may contribute to understanding of urinary continence mechanism and disorders after pelvic floor surgery and obstetrical trauma.